Lembar Kegiatan Peserta Didik Dengan Pendekatan Saintifik Materi Hidrokarbon dan Minyak Bumi - Hartina, Bq; Laksmiwati, Dwi; Anwar, Yunita Arian Sani (FKIP University of Mataram, 2024)
This study aims to determine the validity and practicality of student activity sheets with a scientific approach to hydrocarbon and petroleum materials for class XI High School that have been developed. This type of research is a research and development R&D (Research and Development) 4D model offered by Thiagarajan which consists of four stages, namely the definition stage, the design stage, the development stage and the dissemination stage. LKPD validation is carried out by validators. The results show that the validity of the LKPD that has been assessed by the validators in the content aspect is in the very valid category with an average percentage value of 88.3%, the display aspect is 88.19% with a very valid category, the language aspect is 91.7 % with a very valid category, and aspects of use and presentation of 82.14% with a fairly valid category. The practicality of the LKPD is known from the student response questionnaires. The results of the student response questionnaire obtained an average percentage value of 82% with a very practical category. The results of this study indicate that the student activity sheet with a scientific approach to the material of hydrocarbons and petroleum in class XI High School which was developed is valid and practical to be used as teaching material in chemistry learning in class.